2018
DOI: 10.30773/pi.2017.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Culture of Organotypic Hippocampal Slice from Old 3xTg-AD Mouse: An ex vivo Model of Alzheimer’s Disease

Abstract: Objective Conventional methods for organotypic hippocampal tissue slice culture (OHSC) have shown several disadvantages or limitations regarding age of animals used, duration of culture and difficulty using neurodegenerative models. Therefore, we tried to establish OHSC from old 3xTg-Alzheimer’s disease (AD) mice for longer period (over 4 weeks) and to validate utility of this system as a valid platform for translational neuroscience of AD. Methods OHSC was performed with old 3xTg-AD mice (12–14 months), old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Recently, Jang et al (2018) established organotypic cultures derived from old transgenic animals to study AD, where the slices are grown in serum-free media for 4 weeks. In our work, we established OHCs from 6- and 12-months-old C57Bl/6 animals with serum and demonstrated the ability of bradykinin to maintain viable cultures over a long period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jang et al (2018) established organotypic cultures derived from old transgenic animals to study AD, where the slices are grown in serum-free media for 4 weeks. In our work, we established OHCs from 6- and 12-months-old C57Bl/6 animals with serum and demonstrated the ability of bradykinin to maintain viable cultures over a long period.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of glutamate-mediated excitotoxicity plays a central role in acute and chronic neurodegenerations and represents a target for new therapeutic approaches in numerous pathological states, including cerebral ischemia, stroke, traumatic brain injury [35,36,37]. Organotypic hippocampal slice cultures represent a useful in vitro model with which to study not only the effects of excitotoxicity (triggered by the challenge with NMDA) on nervous cell metabolism and functions [38] but also to evaluate efficacy of drug treatments [39].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Humpel suggests culturing thinner slices (100–150 µm) from adults [ 82 ]. Other authors have found that adult mouse brain slices have greater viability with serum-free medium [ 83 , 84 ]. Treatment of slices with brain-derived neurotrophic factor has also proven beneficial [ 85 ].…”
Section: Suggestions For Future Investigationmentioning
confidence: 99%